Characteristics of decision-making process during prescribing in general practice - Đorđević Nataša D.; Janković Slobodan M. (Vojnosanitetski Pregled)
Background/Aim. The process of prescribing decision-making by general practitioners requires numerous consultations in order to obtain maximal effects, minimal risks, and cost-effectiveness with the full appreciation of a patient's right to choose. The aim of our study was to describe the process of decision-making by general practitioners who decide on the treatment for an individual patient, and to relate the scope and nature of this process to the quality of the outcome of the decision. Methods. The study involved 53 general practitioners who worked in the Health Center, Kragujevac at the time of investigation (September-December 2002.). General practitioners made prescribing decisions, thinking aloud, for five patients with urinary tract infections (n = 2), or stomach complaints (n = 3). The resulting 265 transcripts were analyzed to determine the scope and nature of the decision-making processes. Differences in prescribing were related to the case or the practitioners′ working experience, and to their educational background. Results. Our results showed that the more years of practice the practitioners had the less treatments they prescribed, and the less additional aspects before prescribing they considered. The doctors with less experience, in most of the cases, considered the core aspects, while those with more experience more often considered the contextual and habitual aspects. Educational background of the general practitioners, and the type of a considered disease, had an influence on the decision-making process. The most optimal method for decision-making (marked as type F) was mostly used by the practitioners with the least experience, while the those with more experience mainly made their decisions in the ways considered the least acceptable. The optimal method for decision-making process does not necessarily provide the optimal therapy, so the least acceptable decision-making might not result in an inappropriate treatment. Conclusions. The observed prescribing decisions were mostly in disagreement with the Good Clinical Practice. Our study pointed out the need for the obligatory continuation of medical education of general practitioners in decision-making process during prescribing.